Reducing Sex Differences in Children's Empathy for Animals Through a Training Intervention. Issue 3 (2nd July 2016) - Angantyr, Malin; Hansen, Eric M.; Eklund, Jakob Håkansson; Malm, Kerstin
ABSTRACT: Humane education programs designed to increase children's empathy for animals are becoming more common. A quasi-experiment tested the effectiveness of one such program by comparing 80 children who had completed the program with a control group of 57 children who had not. The children read a story involving an injured dog and rated the degree of empathic concern they felt for him. The results showed that girls tended to express more empathy for a dog than did boys, but this difference was not significant for children who underwent an animal empathy training program. This suggests that humane education programs can reduce sex differences by increasing boys' empathy.